PERAN GURU DALAM MENINGKATKAN KARAKTER DISIPLIN SISWA PASCA PANDEMI COVID-19 - Rizta Rahmatin Febrian; Ratna Sari; Puji Alim (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This research aims to examine the role of teachers in improving students’ disciplinary character after the Covid-19 pandemic in a private high school in Yogyakarta. This research uses qualitative research with triangulation of data sources. The subjects in this research included the school principal, head of student affairs, guidance, and counseling teacher (BK), homeroom teacher for classes X and XI and 2 students. Collecting data, researchers used observation, interviews, and documentation methods. The research results show that, (1) there are four teacher roles, namely a) teacher as guide, b) teacher as educator, c) teacher as motivator, and d) teacher as role model. With the role of teachers, they can provide information about rules and advise perpetrators, thereby increasing student discipline. This increase in discipline is formed due to the habit of carrying out the rules given by the teacher both written and verbally. (2) supporting and inhibiting factors in improving students' disciplinary character after the Covid-19 pandemic at the research location, including supporting factors: a) the role of the family, because the role of the family has quite an important role in implementing discipline when children are in the home environment. b) the role of the educator, because in this case an educator is also important in implementing discipline when children are in the school environment. c) the role within oneself that has awareness and motivation. Meanwhile, the inhibiting factors are a) the role of the family, because in character formation the family plays a big role, and children are also the main priority. b) the role of peers, and c) the role of the environment, because in these two cases it is also very influential in the formation of disciplinary character.